Dinamika Fatwa Bunga Bank di Indonesia: Kajian Terhadap Fatwa MUI, Muhammaddiyah dan Nahdhatul Ulama - Muhammad Yasir Yusuf (Sharia and Law Faculty, 2012)
Islamic banking and finance has experienced tremendous development and impressive achievement in Indonesia even though there is no consensus among Shari’ah scholars on the position of interest banking. This paper will observe the various perspectives of Indonesian Shari’ah scholars’s and analyze the dynamics of fatwa issued on banking interest by three main Islamic organizations in Indonesia, namely; MUI, Muhammadiyah and Nahdhatul Ulama. The paper will also attempt to look to what extent the scholars have contributed to the development of shariah banking in Indonesia. The fatwas are gathered from the resolutions issued by respective organizations in their meeting which have been evolving along with the development of shariah banking in Indonesia.